Inside Back Cover: Tailored Fabrication of Transferable and Hollow Weblike Titanium Dioxide Structures (ChemPhysChem 1/2017). Issue 1 (4th January 2017) - Hiltunen, Arto; Lahtonen, Kimmo; Saari, Jesse; Ojanperä, Anniina; Sarlin, Essi; Wondraczek, Holger; Efimov, Alexander; Kaunisto, Kimmo; Vivo, Paola; Maccato, Chiara; Barreca, Davide; Fardim, Pedro; et al.
Abstract : The Inside Back Cover picture shows a weblike titanium dioxide thin film, which was prepared by applying atomic layer deposition on porous cellulose acetate templates. In the amorphous form the web is flexible, and can be transferred to a new substrate. Crystallization of TiO2 is achieved by heating. More information can be found in the Full Paper by A. Hiltunen et al. onpage 64 in Issue 1, 2017 (DOI:10.1002/cphc.201600930 ).